Analysis of infant mortality from preventable causes in Paraná, 2010-2020 (Research, Society and Development, 2023)
The infant mortality rate reflects multiple aspects of the health of a population, so this study aimed to analyze infant mortality, following preventability criteria, in the state of Paraná from 2010 to 2020. It was a descriptive study with a quantitative approach with based on secondary data from the Mortality Information System and the Live Birth Information System, available in the Information Technology Department of the Unified Health System. The following variables were used: number and percentage of infant deaths in children under 5 years of age due to preventable causes, ill-defined and not clearly preventable causes; age group, race/color and sex. Data were collected, analyzed and tabulated in Microsoft Office Excel spreadsheets. During the period and location studied, 21,442 deaths were recorded, 63% were due to preventable causes, mainly due to ineffective care for pregnant women and newborns, in white and male cases. 45.8% of children died in the first week of life. This scenario of preventable deaths demonstrates the need to strengthen Public Policies aimed at health care for mother and child, as well as improving access to health services and intersectorality as an essential factor in reducing health inequities.